Analysis of Xanthine Oxidase Inhibitors from Puerariae flos Using Centrifugal Ultrafiltration Coupled with HPLC-MS - Liu,Liangliang (2017)
In this study, centrifugal ultrafiltration coupled with high performance liquid chromatography-mass spectrometry was utilized to screen and identify xanthine oxidase inhibitors from Puerariae flos extract. The experimental conditions of centrifugal ultrafiltration including xanthine oxidase concentration, incubation time, pH and temperature were optimized. At the optimum condition (xanthine oxidase concentration: 30.0 μg mL-1, incubation time: 20 min, pH 7.0 and temperature: 25 ºC), four compounds were successfully screened from P. flos extract and identified as tectoridin, daidzin, ononin and biochanin A. The yields of tectoridin, daidzin, ononin and biochanin A were 0.231, 0.117, 0.303 and 0.089 g from 50.0 g crude P. flos samples. The inhibitory activities of these compounds were verified by xanthine oxidase inhibition assays. The experimental half maximal inhibitory concentration (IC50) values of tectoridin, daidzin, ononin and biochanin A were 88.5, 85.1, 88.8 and 87.0 μmol L-1, and the binding degree of them were 5.70, 8.28, 6.31 and 37.83% at the optimum condition, respectively. The proposed method provided a rapid and effective way to screen and analyze active compounds from natural products.